A collaborative evaluation method of the quality of patent scientific and technological resources. (December 2021) - Wu, Yingwen; Ji, Yangjian; Gu, Fu; Guo, Jianfeng
Abstract: A justified patent quality evaluation method is critical to improving the sharing efficiency of scientific and technological resources in online platforms. We propose a collaborative evaluation method of the quality of patent scientific and technological resources, combining the subjective evaluation results from the collaborative evaluation and the objective evaluation results. Firstly, an index system of patent quality is established, with the values of three dimensions, i.e., technical, legal, and market, considered. Then a collaborative evaluation model of patent quality based on the index system is proposed. Finally, a patent quality evaluation system is developed to support the collaborative evaluation process of patent quality. Our approach improves the comprehensiveness and efficiency of patent quality evaluation, and thereby facilitates the construction and development of regional scientific and technological resources sharing platforms.